Analisis Faktor Penyebab Menurunnya Pendidikan Akhlak Pada Remaja di Desa Laut Dendang, Kecamatan Percut Sei Tuan, Kabupaten Deli Serdang - Syapitri, Syapitri; Arifin, Zainal (Cetta: Jurnal Ilmu Pendidikan, 2024)
Changes in increasingly sophisticated times have resulted in increasingly visible moral changes. This is due to the entry of foreign culture, namely western culture, into Indonesia, thereby erasing the original Indonesian culture itself. The aim of this research is to find out what factors cause the decline in morals in teenagers, then analyze these factors to find solutions that can be provided to help improve the morals of teenagers today. This research used a qualitative descriptive method, with data collection techniques in the form of interviews, observation and documentation by taking a sample of 13 sources, especially teenagers aged 12 to 17 years. The data analysis technique used is Miles and Huberman's theory, including data reduction, presentation of data, and drawing conclusions. The research results show that the factors causing the decline in morals in teenagers are influenced by two factors, namely internal factors in the form of willingness and desire to play social media, and internal factors in the form of family and peer relationships. The solution that can be given to overcome the decline in morals in teenagers which is considered effective is to instill religious education from an early age using the exemplary method.